Effect of Micropores of a Porous Coordination Polymer on the Product Selectivity in RuII Complex‐catalyzed CO2 Reduction. Issue 21 (22nd September 2021) - Kajiwara, Takashi; Ikeda, Miyuki; Kobayashi, Katsuaki; Higuchi, Masakazu; Tanaka, Koji; Kitagawa, Susumu
Abstract: To develop an efficient CO2 reduction catalyst, hybridizing a molecular catalyst and a porous coordination polymer (PCP) is a promising strategy because it can combine both advantages of the precise reactivity control of the former and the CO2 adsorption property of the latter. Although several PCP hybrid catalysts have been reported to date, the CO2 sorption behavior and the CO2 reduction reactivity have been investigated separately, and the CO2 enrichment during the catalysis is still unclear. We report CO2 photoreduction under different temperatures and pressures using a PCP‐RuII complex hybrid catalyst. The product selectivity (CO or HCOOH) varied depending on the reaction conditions. The altered selectivity could be interpreted in terms of the CO2 capture in the micropores of a PCP. Abstract : CO2 photoreduction by using a porous coordination polymer (PCP)‐Ru II complex hybrid catalyst under various reaction conditions were investigated to find that the PCP hybrid catalyst showed higher CO selectivity compared with the corresponding homogeneous Ru II complex. The altered selectivity was attributed to the higher local CO2 concentration around the catalytic center due to the CO2 capture in the micropores of a PCP.